Descriptive Study on the Relationship between Social Interaction, Motivation, and Learning Skills of Elementary School Students - Kosilah; Suarti; Onde, Mitra Kasih La Ode; Yurfiah (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
The success of elementary education is determined not only by cognitive instruction but also by the development of students’ social interaction, learning motivation, and learning skills. These three aspects are interrelated and play a vital role in supporting effective learning behavior. This study aims to describe the relationship between social interaction, learning motivation, and learning skills among elementary school students. A quantitative descriptive method was applied, involving a randomly selected group of 27 students. Data were collected through a validated questionnaire and analyzed with statistical software using descriptive tests, normality tests, and correlation tests. The findings show that all variables fall into the high category with normally distributed data. The study also reveals a strong and significant positive relationship between social interaction, learning motivation, and learning skills. These results highlight that students with stronger social engagement and higher learning motivation tend to demonstrate better learning skills. This study emphasizes the importance of creating a learning environment that fosters social development and enhances motivation in order to optimize both academic and personal growth at the elementary education level.